Effect of Supervision on Performance Employees at Regional Technical Implementation Unit (RTIU) Senaken Penyembolum Market, Paser District - Nuriyah, Nuriyah; Akbar, Muhammad; Hidayah, Welda Widya (PT. Riset Press International, 2024)
The aim of this research is to determine the effect of supervision on employee performance at the Regional Technical Implementation Unit (RTIU) Pemembolum Senaken Market, Paser Regency. From the results of the validity test, all 10 statement items were declared valid because they were greater than the rtable value of 0.2006 for each statement in this study. From the results of the reliability test, a value of 0.959 was obtained, which means there is a very strong relationship between the independent variable and the dependent variable. From the results of multiple linear regression analysis, it can be seen that the results of the regression equation are Y = 40.597 + 0.535X1 + 0.361X2. Based on the calculation results, an R value (Correlation Coefficient) of 0.915 is obtained which is at an interpretation level between 0.80-1.00, which means that there is a very strong influence from the supervision variable (X) which consists of direct supervision (X1), and supervision. indirectly (X2), on employee performance (Y). The value of the Adjusted R Square Determination Coefficient (????2) is 0.833 or 83.3%. These results show that 83.3% of the direct supervision variables (X1) and indirect supervision (X2) have had an influence on the employee performance variable (Y). The remaining 16.7% is influenced by other unknown variables. From the results of the F test carried out, the supervision variable (X) consists of direct supervision (X1) and indirect supervision (X2), together they have an influence on employee performance. This is proven by the Fcount result of 238.507 with a significance level of 0.000, which means it is greater than Ftable 3.09. The results of the t test showed that the t-count value of direct supervision (X1) was 5.646 with a significant level of 0.000 and the t-count value of indirect supervision (X2) was 3.637 with a significance level of 0.000. Of the two independent variables studied, it is known that the direct supervision variable (X1) is the variable that has the dominant influence on employee performance (Y). This is proven by the results of direct supervision (X1) > indirect supervision (X2) or (5.646 > 3.637) so H0 is rejected and Ha is accepted.